Zinc battery

JP2023133607A5Active Publication Date: 2025-04-04ENERGYWITH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023127866
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-04-04
Estimated Expiration
2038-11-19

AI Technical Summary

Technical Problem

Zinc batteries face issues with dendrite formation leading to short circuits and decreased life performance due to side reactions during charging and discharging, necessitating improved high-rate discharge performance and suppression of side reactions.

Method used

An electrolyte solution containing potassium hydroxide and optionally sodium hydroxide or lithium hydroxide, along with specific separator air permeability, is used to enhance high-rate discharge performance and suppress side reactions.

Benefits of technology

The solution provides a zinc battery with excellent high-rate discharge performance and reduced side reactions, improving life performance by preventing dendrite formation and minimizing oxygen absorption.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a zinc battery having an excellent high-rate discharge performance and suppressed in the side reaction during charge and discharge.SOLUTION: An electrolyte solution for a zinc battery consists of an aqueous solution comprising potassium hydroxide, and at least one kind selected from a group consisting of sodium hydroxide and lithium hydroxide.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrolyte for a zinc battery and a zinc battery.

Background Art

[0002] As zinc batteries, nickel-zinc batteries, air-zinc batteries, silver-zinc batteries, etc. are known. For example, since a nickel-zinc battery is an aqueous battery using an aqueous electrolyte such as an aqueous potassium hydroxide solution, it has high safety, and it is known that it has a high electromotive force as an aqueous battery due to the combination of a zinc electrode and a nickel electrode. Furthermore, since a nickel-zinc battery has excellent input / output performance and is low in cost, its applicability to industrial applications (for example, applications such as backup power sources) and automotive applications (for example, applications such as hybrid vehicles) has been studied.

[0003] The charge-discharge reaction of a nickel-zinc battery proceeds, for example, according to the following formula (discharge reaction: rightward, charge reaction: leftward). (Positive electrode) 2NiOOH + 2H2O + 2e , , 2- ,

[0003] , - , - , - , , - , ,

[0004] , → 2Ni(OH)2 + 2OH - (Negative electrode) Zn + 2OH - → Zn(OH)2 + 2e -

[0004] As shown in the above formula, in a zinc battery, zinc hydroxide (Zn(OH)2) is generated by a discharge reaction. Zinc hydroxide is soluble in the electrolyte, and when zinc hydroxide dissolves in the electrolyte, tetra-hydroxide zincate ion ([Zn(OH)4 2-) diffuses into the electrolyte. As a result, the negative electrode undergoes a change in shape (deformation) and the distribution of the charging current becomes uneven, causing localized zinc deposition on the negative electrode and the formation of dendrites (dendritic crystals). In conventional zinc batteries, if dendrites grow due to repeated charging and discharging, the dendrites may penetrate the separator and cause a short circuit. Therefore, various attempts have been made to prevent such short circuits caused by dendrites and improve battery life. For example, Patent Document 1 below discloses a technique for preventing short circuits caused by dendrites by interposing a nickel-plated nonwoven fabric between the electrodes. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 58-126665 [Overview of the project] [Problems that the invention aims to solve]

[0006] During the charging and discharging of nickel-zinc batteries, side reactions such as electrolyte decomposition may occur. Since the occurrence of these side reactions leads to a decrease in battery life, it is necessary to suppress their occurrence. Furthermore, zinc batteries are required to have improved high-rate discharge performance in addition to improved battery life.

[0007] Therefore, the present invention aims to provide a zinc battery that has excellent high-rate discharge performance and suppresses side reactions during charging and discharging. [Means for solving the problem]

[0008] One aspect of the present invention is an aqueous solution for a zinc battery containing potassium hydroxide and at least one substance selected from the group consisting of sodium hydroxide and lithium hydroxide. This electrolyte can improve the high-rate discharge performance of a zinc battery and suppress the occurrence of side reactions during charging and discharging.

[0009] Another aspect of the present invention is a zinc battery comprising the above-mentioned electrolyte. This zinc battery provides excellent high-rate discharge performance and is less prone to side reactions during charging and discharging.

[0010] Preferably, the zinc battery further comprises one or more separators having a total air permeability of 500 to 2500 sec / 100 mL, and adjacent positive and negative electrodes separated by the one or more separators. When the total air permeability of the separators placed between adjacent positive and negative electrodes is within the above range, the occurrence of short circuits due to dendrites is more easily suppressed, and better life performance (e.g., cycle life performance) is more easily obtained. Furthermore, in the present invention, since the amount of oxygen produced as a result of side reactions (decomposition reactions of the electrolyte) is reduced, even if the total air permeability of the separators is within the above range, the amount of oxygen discharged outside the system without being absorbed by the negative electrode is small. In other words, the decrease in electrolyte is less likely to occur.

[0011] Preferably, at least one of the one or more separators described above has an air permeability of 0.1 to 150 sec / 100 mL. In this case, it is easier to obtain better high-rate discharge performance and lifespan performance. [Effects of the Invention]

[0012] According to the present invention, it is possible to provide a zinc battery that has excellent high-rate discharge performance and suppresses side reactions during charging and discharging. [Modes for carrying out the invention]

[0013] In this specification, numerical ranges indicated using "~" represent a range that includes the numbers before and after "~" as the minimum and maximum values, respectively. In numerical ranges described stepwise in this specification, the upper or lower limit of a numerical range in one step can be arbitrarily combined with the upper or lower limit of a numerical range in another step. In numerical ranges described in this specification, the upper or lower limit of that numerical range may be replaced with the values ​​shown in the experimental examples. "A or B" means that either A or B is included, or both are included. Unless otherwise specified, the materials exemplified in this specification can be used individually or in combination of two or more. In this specification, the amount of each component used in a composition means the total amount of multiple substances present in the composition if there are multiple substances corresponding to each component in the composition, unless otherwise specified. Furthermore, in this specification, the terms "film" or "layer" include not only structures that are formed on the entire surface when observed as a plan view, but also structures that are formed on only a part of it. Furthermore, in this specification, the term "process" includes not only independent processes, but also processes that cannot be clearly distinguished from other processes, as long as their intended function is achieved.

[0014] Preferred embodiments of the present invention will be described below. However, the present invention is not limited in any way to the embodiments described below.

[0015] <Electrolyte for zinc batteries> [First Embodiment] The electrolyte of the first embodiment is an aqueous solution containing potassium hydroxide and sodium hydroxide as electrolytes. Potassium hydroxide and sodium hydroxide may be ionized in the aqueous solution and may exist as salts. For example, deionized water can be used as the solvent for the electrolyte.

[0016] The concentration (content) of potassium hydroxide in the electrolyte may be 3% by mass or more, 10% by mass or more, or 15% by mass or more based on the total mass of the electrolyte from the viewpoint of further excellent high-rate discharge performance. The concentration of potassium hydroxide in the electrolyte may be 35% by mass or less, 30% by mass or less, or 25% by mass or less based on the total mass of the electrolyte from the viewpoint of further suppressing side reactions.

[0017] The concentration (content) of sodium hydroxide in the electrolyte may be 1% by mass or more, 3% by mass or more, or 5% by mass or more based on the total mass of the electrolyte from the viewpoint of further suppressing side reactions. The concentration of sodium hydroxide in the electrolyte may be 25% by mass or less, 15% by mass or less, or 10% by mass or less based on the total mass of the electrolyte from the viewpoint of further excellent high-rate discharge performance.

[0018] The total content of potassium hydroxide and sodium hydroxide in the electrolyte may be 12% by mass or more, 15% by mass or more, or 18% by mass or more, and may be 35% by mass or less, 30% by mass or less, or 28% by mass or less based on the total mass of the electrolyte from the viewpoints of further excellent high-rate discharge performance and further suppressing side reactions.

[0019] The concentration (content) of the electrolyte in the electrolyte may be 12% by mass or more, 15% by mass or more, or 18% by mass or more, and may be 35% by mass or less, 30% by mass or less, or 28% by mass or less based on the total mass of the electrolyte from the viewpoints of further excellent high-rate discharge performance and further suppressing side reactions.

[0020] The electrolyte may further contain potassium phosphate, potassium fluoride, potassium carbonate, sodium phosphate, sodium fluoride, lithium hydroxide, zinc oxide, antimony oxide, titanium dioxide, nonionic surfactant, anionic surfactant, etc.

[0021] [Second Embodiment] The electrolytic solution of the second embodiment is an aqueous solution containing potassium hydroxide and lithium hydroxide as electrolytes. Potassium hydroxide and lithium hydroxide may be ionized in the aqueous solution or may exist as salts. As the solvent of the electrolytic solution, for example, ion-exchanged water can be used.

[0022] From the viewpoint of further excellent high-rate discharge performance, the concentration (content) of potassium hydroxide in the electrolytic solution may be 15% by mass or more, 18% by mass or more, or 20% by mass or more based on the total mass of the electrolytic solution. From the viewpoint of further suppressing side reactions, the concentration of potassium hydroxide in the electrolytic solution may be 35% by mass or less, 30% by mass or less, or 25% by mass or less based on the total mass of the electrolytic solution.

[0023] From the viewpoint of further suppressing side reactions, the concentration (content) of lithium hydroxide in the electrolytic solution may be 0.01% by mass or more, 0.1% by mass or more, or 0.2% by mass or more based on the total mass of the electrolytic solution. From the viewpoint of further excellent high-rate discharge performance, the concentration of lithium hydroxide in the electrolytic solution may be 10% by mass or less, 5% by mass or less, or 3% by mass or less based on the total mass of the electrolytic solution.

[0024] From the viewpoints of further excellent high-rate discharge performance and further suppressing side reactions, the total content of potassium hydroxide and lithium hydroxide in the electrolytic solution may be 12% by mass or more, 15% by mass or more, or 18% by mass or more based on the total mass of the electrolytic solution, and may be 35% by mass or less, 30% by mass or less, or 28% by mass or less.

[0025] From the viewpoints of further excellent high-rate discharge performance and further suppressing side reactions, the concentration (content) of the electrolyte in the electrolytic solution may be 12% by mass or more, 15% by mass or more, or 18% by mass or more based on the total mass of the electrolytic solution, and may be 35% by mass or less, 30% by mass or less, or 28% by mass or less.

[0026] The electrolyte may further contain potassium phosphate, potassium fluoride, potassium carbonate, sodium phosphate, sodium fluoride, sodium hydroxide, zinc oxide, antimony oxide, titanium dioxide, nonionic surfactants, anionic surfactants, etc.

[0027] [Third Embodiment] The electrolyte of the third embodiment is an aqueous solution containing potassium hydroxide, sodium hydroxide, and lithium hydroxide as the electrolyte. Potassium hydroxide, sodium hydroxide, and lithium hydroxide may be ionized in the aqueous solution and may exist as salts. For example, deionized water can be used as the solvent for the electrolyte.

[0028] The concentration (content) of potassium hydroxide in the electrolyte may be 3% by mass or more, 10% by mass or more, or 15% by mass or more, based on the total mass of the electrolyte, from the viewpoint of further improving high-rate discharge performance. The concentration of potassium hydroxide in the electrolyte may be 35% by mass or less, 30% by mass or less, or 25% by mass or less, based on the total mass of the electrolyte, from the viewpoint of further suppressing side reactions.

[0029] The concentration (content) of sodium hydroxide in the electrolyte may be 1% by mass or more, 3% by mass or more, or 5% by mass or more, based on the total mass of the electrolyte, from the viewpoint of further suppressing side reactions. The concentration of sodium hydroxide in the electrolyte may be 25% by mass or less, 15% by mass or less, or 10% by mass or less, based on the total mass of the electrolyte, from the viewpoint of further improving high-rate discharge performance.

[0030] The concentration (content) of lithium hydroxide in the electrolyte may be 0.01% by mass or more, 0.1% by mass or more, or 0.2% by mass or more, based on the total mass of the electrolyte, from the viewpoint of further suppressing side reactions. The concentration of lithium hydroxide in the electrolyte may be 10% by mass or less, 5% by mass or less, or 3% by mass or less, based on the total mass of the electrolyte, from the viewpoint of further improving high-rate discharge performance.

[0031] The total content of potassium hydroxide, sodium hydroxide, and lithium hydroxide in the electrolyte may be 12% by mass or more, 15% by mass or more, or 18% by mass or more, and 35% by mass or less, 30% by mass or less, or 25% by mass or less, based on the total mass of the electrolyte, from the viewpoint of further improving high-rate discharge performance and further suppressing side reactions.

[0032] The concentration (content) of the electrolyte in the electrolyte solution may be 12% by mass or more, 15% by mass or more, or 18% by mass or more, and may be 35% by mass or less, 30% by mass or less, or 25% by mass or less, based on the total mass of the electrolyte solution, from the viewpoint of further improving high-rate discharge performance and further suppressing side reactions.

[0033] The electrolyte may further contain potassium phosphate, potassium fluoride, potassium carbonate, sodium phosphate, sodium fluoride, zinc oxide, antimony oxide, titanium dioxide, nonionic surfactants, anionic surfactants, etc.

[0034] The electrolytes of the first to third embodiments described above are electrolytes for zinc batteries (e.g., zinc secondary batteries) that are incorporated into zinc batteries. Examples of zinc batteries include nickel-zinc batteries and zinc-air batteries. In zinc batteries, a zinc negative electrode can be used. Below, a nickel-zinc battery will be described as an example of a zinc battery in which the electrolytes of the above embodiments are used.

[0035] <Nickel-zinc battery> The nickel-zinc battery of this embodiment (for example, a nickel-zinc secondary battery) comprises, for example, a battery case, an electrode group (for example, an electrode plate group) and an electrolyte housed in the battery case. The zinc battery of this embodiment may be either post-chemically modified or un-chemically modified.

[0036] The electrode group comprises, for example, a positive electrode (e.g., a positive electrode plate), a negative electrode (e.g., a negative electrode plate), and a separator. The positive electrode and the negative electrode are adjacent to each other, separated by one or more separators. That is, one or more separators are provided between adjacent positive and negative electrodes. The electrode group may comprise multiple positive electrodes, negative electrodes, and separators. When the electrode group comprises multiple positive electrodes and / or multiple negative electrodes, the positive and negative electrodes may be stacked alternately via separators. Multiple positive electrodes and multiple negative electrodes may be connected to each other, for example, by straps. In this embodiment, the positive electrode is a nickel (Ni) electrode, and the negative electrode is a zinc (Zn) electrode. That is, in the following description, "positive electrode" may be replaced with "nickel electrode," and "negative electrode" may be replaced with "zinc electrode." The same applies to descriptions of "positive electrode material," "negative electrode material," etc.

[0037] The positive electrode comprises, for example, a positive electrode current collector and a positive electrode material supported by the positive electrode current collector. The positive electrode may be either pre-chemical or post-chemical.

[0038] The positive electrode current collector constitutes the conductive path for the current from the positive electrode material. The positive electrode current collector has a shape such as a flat plate or a sheet. The positive electrode current collector may also be a current collector with a three-dimensional mesh structure composed of foamed metal, expanded metal, perforated metal, felt-like material of metal fibers, etc. The positive electrode current collector is made of a material that has conductivity and alkali resistance. As such a material, for example, a material that is stable even at the reaction potential of the positive electrode (a material having an oxidation-reduction potential nobler than the reaction potential of the positive electrode, a material that forms a protective film such as an oxide film on the surface of the substrate in an alkaline aqueous solution to stabilize it, etc.) can be used. In addition, at the positive electrode, a decomposition reaction of the electrolyte proceeds as a side reaction and oxygen gas is generated, but a material with a high oxygen overpotential is preferable in that it can suppress the progress of such a side reaction. Specific examples of materials that constitute the positive electrode current collector include platinum; nickel (foamed nickel, etc.); and metal materials with metal plating such as nickel (copper, brass, steel, etc.). Among these, a positive electrode current collector made of foamed nickel is preferably used. From the viewpoint of further improving high-rate discharge performance, it is preferable that at least the portion of the positive electrode current collector that supports the positive electrode material (positive electrode material support portion) is made of foamed nickel.

[0039] The positive electrode material may, for example, be layered. That is, the positive electrode may have a positive electrode material layer. The positive electrode material layer may be formed on the positive electrode current collector. If the positive electrode material support portion of the positive electrode current collector has a three-dimensional mesh structure, the positive electrode material may be filled between the mesh of the current collector to form the positive electrode material layer.

[0040] The positive electrode material contains a positive electrode active material (electrode active material) containing nickel. Examples of positive electrode active materials include nickel oxyhydroxide (NiOOH) and nickel hydroxide. For example, the positive electrode material contains nickel oxyhydroxide in the fully charged state and nickel hydroxide in the discharged state. The content of the positive electrode active material may be, for example, 50 to 95% by mass based on the total mass of the positive electrode material.

[0041] The positive electrode material may further contain other components besides the positive electrode active material as additives. Examples of additives include binders, conductive agents, and swelling inhibitors.

[0042] Examples of binders include hydrophilic or hydrophobic polymers. Specifically, for example, carboxymethylcellulose (CMC), hydroxyethylcellulose (HEC), hydroxypropylmethylcellulose (HPMC), sodium polyacrylate (SPA), and fluorine-based polymers (such as polytetrafluoroethylene (PTFE)) can be used as binders. The binder content is, for example, 0.01 to 5 parts by mass per 100 parts by mass of positive electrode active material.

[0043] Examples of conductive agents include cobalt compounds (metallic cobalt, cobalt oxide, cobalt hydroxide, etc.). The content of the conductive agent is, for example, 1 to 20 parts by mass per 100 parts by mass of positive electrode active material.

[0044] Examples of expansion inhibitors include zinc oxide. The amount of expansion inhibitor is, for example, 0.01 to 5 parts by mass per 100 parts by mass of positive electrode active material.

[0045] The negative electrode comprises a negative electrode current collector (current collector) and a negative electrode material (electrode material) supported by the negative electrode current collector. The negative electrode may be either pre-chemical or post-chemical.

[0046] The negative electrode current collector constitutes the conductive path for the current from the negative electrode material. The negative electrode current collector has a shape such as a flat plate or a sheet. The negative electrode current collector may also be a current collector with a three-dimensional mesh structure composed of foamed metal, expanded metal, perforated metal, felt-like material of metal fibers, etc. The negative electrode current collector is made of a material that has conductivity and alkali resistance. As such a material, for example, a material that is stable even at the reaction potential of the negative electrode (a material having an oxidation-reduction potential nobler than the reaction potential of the negative electrode, a material that forms a protective film such as an oxide film on the substrate surface in an alkaline aqueous solution to stabilize it, etc.) can be used. In addition, at the negative electrode, a decomposition reaction of the electrolyte proceeds as a side reaction and hydrogen gas is generated, but a material with a high hydrogen overpotential is preferable in that it can suppress the progress of such a side reaction. Specific examples of materials that constitute the negative electrode current collector include metal materials with metal plating such as zinc, lead, tin, etc. (copper, brass, steel, nickel, etc.).

[0047] The negative electrode material may, for example, be layered. That is, the negative electrode may have a negative electrode material layer. The negative electrode material layer may be formed on the negative electrode current collector. If the portion of the negative electrode current collector that supports the negative electrode material has a three-dimensional mesh structure, the negative electrode material may be filled between the mesh of the current collector to form the negative electrode material layer.

[0048] The negative electrode material contains a negative electrode active material (electrode active material) containing zinc. Examples of negative electrode active materials include metallic zinc, zinc oxide, and zinc hydroxide. The negative electrode active material may contain one of these components alone or multiple components. For example, the negative electrode material contains metallic zinc in the fully charged state and zinc oxide and zinc hydroxide in the discharged state. The negative electrode active material is, for example, particulate. That is, the negative electrode material may contain at least one selected from the group consisting of metallic zinc particles, zinc oxide particles, and zinc hydroxide particles. The content of the negative electrode active material is, for example, 50 to 95% by mass based on the total mass of the negative electrode material.

[0049] The negative electrode material may contain additives. Examples of additives include binders and conductive agents.

[0050] Examples of binders include polytetrafluoroethylene, hydroxyethylcellulose, polyethylene oxide, polyethylene, and polypropylene. The binder content may be, for example, 0.5 to 10 parts by mass per 100 parts by mass of the negative electrode active material.

[0051] Examples of conductive agents include indium compounds (such as indium oxide). The content of the conductive agent is, for example, 1 to 20 parts by mass per 100 parts by mass of the negative electrode active material.

[0052] The separator may have a shape such as a flat plate or a sheet. Examples of separators include polyolefin-based microporous membranes, nylon-based microporous membranes, oxidation-resistant ion exchange resin membranes, cellophane-based recycled resin membranes, inorganic-organic separators, and polyolefin-based nonwoven fabrics.

[0053] The total air permeability of the separator is preferably 500 to 2500 sec / 100 mL from the viewpoint of further superior high-rate discharge performance and superior life performance (e.g., cycle life performance). From the viewpoint of further superior cycle life performance, the total air permeability of the separator is more preferably 1000 sec / 100 mL or more, even more preferably 1200 sec / 100 mL or more, particularly preferably 1300 sec / 100 mL or more, and most preferably 1350 sec / 100 mL or more. From the viewpoint of further superior high-rate discharge performance and further superior cycle life performance, the total air permeability of the separator is more preferably 2000 sec / 100 mL or less, even more preferably 1500 sec / 100 mL or less, and particularly preferably 1400 sec / 100 mL or less. Here, the sum of air permeability refers to the air permeability of one separator if there is one separator, and the sum of the air permeability of each separator if there are multiple separators. Furthermore, the sum of air permeability refers to the sum of the air permeability of the separators provided between adjacent positive and negative electrodes. That is, even if the electrode group has multiple separators, if there is only one separator placed between adjacent positive and negative electrodes, the sum of air permeability refers to the air permeability of one separator. When the electrode group has multiple positive electrodes and / or multiple negative electrodes, it is preferable that the sum of the air permeability of the separators placed in at least one of the spaces formed between adjacent positive and negative electrodes falls within the above range, and it is more preferable that the sum of the air permeability of the separators placed in all spaces falls within the above range.

[0054] Air permeability is a measure of how easily air can pass through a membrane, and can be expressed using the Gurley densometer method as the number of seconds it takes for a certain volume of air to pass through a membrane of a certain area under a constant pressure difference. The air permeability of a separator can be measured using a Gurley densometer (for example, Yasuda Seiki Seisakusho Co., Ltd., product name: No.323 GURLEY TYPE DENSOMETER, membrane area: 642 mm²). 2 It can be measured using a diameter of 28.6 mm.

[0055] When the total air permeability of the separators is 500 to 2500 sec / 100 mL, it is preferable that at least one of the separators has an air permeability of 0.1 to 150 sec / 100 mL. In this case, it is easier to obtain better high-rate discharge performance and lifespan performance. The air permeability of the above separators is more preferably 5.0 sec / 100 mL or more, even more preferably 40 sec / 100 mL or more, and particularly preferably 80 sec / 100 mL or more, in terms of easily obtaining better lifespan performance. The air permeability of the above separators is more preferably 140 sec / 100 mL or less, even more preferably 130 sec / 100 mL or less, and particularly preferably 100 sec / 100 mL or less, in terms of easily obtaining better high-rate discharge performance and lifespan performance.

[0056] The number of separators provided between adjacent positive and negative electrodes is not particularly limited, but three is preferred. Of the three separators, it is preferable that the separator located on the positive electrode side and the separator located on the negative electrode side are microporous membranes, and the separator in the middle is a nonwoven fabric. Of the three separators, it is more preferable that the separator in the middle has the air permeability of 0.1 to 150 sec / 100 mL as described above. In this case, the air permeability of the separator located on the positive electrode side and the separator located on the negative electrode side may be, for example, 500 to 1000 sec / 100 mL.

[0057] The nickel-zinc battery manufacturing method described above comprises, for example, a component manufacturing step for obtaining components of a zinc battery, and an assembly step for assembling the components to obtain a zinc battery. In the component manufacturing step, at least electrodes (positive electrode and negative electrode) are obtained.

[0058] Electrodes can be obtained, for example, by adding a solvent (e.g., water) to the raw materials of the electrode material (positive electrode material and negative electrode material) and kneading them to obtain an electrode material paste (paste-like electrode material), and then forming an electrode material layer using the electrode material paste.

[0059] Examples of raw materials for the positive electrode material include raw materials for the positive electrode active material (e.g., nickel hydroxide) and additives (e.g., the aforementioned binder). Examples of raw materials for the negative electrode material include raw materials for the negative electrode active material (e.g., metallic zinc, zinc oxide, and zinc hydroxide) and additives (e.g., the aforementioned binder).

[0060] One method for forming the electrode material layer is to apply or fill an electrode material paste onto a current collector and then dry it to obtain the electrode material layer. The density of the electrode material layer may be increased by pressing or other means as needed.

[0061] In the assembly process, for example, the positive and negative electrodes obtained in the component manufacturing process are stacked alternately with separators in between, and then the positive electrodes and negative electrodes are connected with straps to create an electrode group. Next, this electrode group is placed in the battery case, and then a lid is glued to the top surface of the battery case to obtain an unformed zinc battery (nickel-zinc battery).

[0062] Next, the electrolyte is injected into the battery case of the unformed zinc battery and left for a certain period of time. Then, a zinc battery (nickel-zinc battery) is obtained by charging under predetermined conditions. The formation conditions can be adjusted according to the properties of the electrode active materials (positive electrode active material and negative electrode active material).

[0063] The above describes an example of a nickel-zinc battery (e.g., a nickel-zinc secondary battery) in which the positive electrode is a nickel electrode. However, a zinc battery may also be an air-zinc battery (e.g., an air-zinc secondary battery) in which the positive electrode is an air electrode, or a silver-zinc battery (e.g., a silver-zinc secondary battery) in which the positive electrode is a silver oxide electrode.

[0064] As the air electrode of a zinc-air battery, a known air electrode used in zinc-air batteries can be used. The air electrode includes, for example, an air electrode catalyst, an electronically conductive material, etc. As the air electrode catalyst, an air electrode catalyst that also functions as an electronically conductive material can be used.

[0065] As the air electrode catalyst, it is possible to use one that functions as the positive electrode in a zinc-air cell, and various air electrode catalysts that can utilize oxygen as the positive electrode active material can be used. Examples of air electrode catalysts include carbon-based materials with redox catalytic function (graphite, etc.), metal materials with redox catalytic function (platinum, nickel, etc.), and inorganic oxide materials with redox catalytic function (perovskite-type oxides, manganese dioxide, nickel oxide, cobalt oxide, spinel oxide, etc.). The shape of the air electrode catalyst is not particularly limited, but may be particulate, for example. The amount of air electrode catalyst used in the air electrode may be 5 to 70% by volume, 5 to 60% by volume, or 5 to 50% by volume, relative to the total amount of air electrode material.

[0066] As the electronically conductive material, any material that is conductive and enables electron conduction between the air electrode catalyst and the separator can be used. Examples of electronically conductive materials include carbon blacks such as Ketjenblack, acetylene black, channel black, furnace black, lamp black, and thermal black; graphites such as natural graphite, artificial graphite, and expanded graphite; conductive fibers such as carbon fibers and metal fibers; metal powders such as copper, silver, nickel, and aluminum; organic electronically conductive materials such as polyphenylene derivatives; and any mixture thereof. The shape of the electronically conductive material may be particulate or other shapes. Preferably, the electronically conductive material is used in a form that provides a continuous phase in the thickness direction at the air electrode. For example, the electronically conductive material may be a porous material. Furthermore, the electronically conductive material may be in the form of a mixture or composite with the air electrode catalyst, or, as mentioned above, the air electrode catalyst may also function as an electronically conductive material. The amount of electronically conductive material used in the air electrode may be 10 to 80 volume%, 15 to 80 volume%, or 20 to 80 volume%, relative to the total volume of the air electrode.

[0067] For the silver oxide electrode of a silver-zinc battery, a known silver oxide electrode used in silver-zinc batteries can be used. The silver oxide electrode contains, for example, silver(I) oxide. [Examples]

[0068] The present invention will be described in more detail below using experimental examples, but the present invention is not limited to the following experimental examples.

[0069] [Preparing the nonwoven fabric] The following nonwoven fabrics 1-6 were prepared. • Nonwoven fabric 1 (manufactured by Nippon Kodo Paper Industry Co., Ltd., product name: VL-100, air permeability: 0.3 sec / 100 mL) • Nonwoven fabric 2 (manufactured by Oji F-Tex Co., Ltd., air permeability: 5.4 sec / 100 mL) • Nonwoven fabric 3 (manufactured by Daio Paper Corporation, product name: Ryuo Moisture Resistant, air permeability: 46.6 sec / 100 mL) • Nonwoven fabric 4 (manufactured by Daio Paper Corporation, product name: foil base paper, air permeability: 84.3 sec / 100 mL) • Nonwoven fabric 5 (manufactured by Daio Paper Corporation, product name: Kinshachi, air permeability: 133.6 sec / 100 mL) • Nonwoven fabric 6 (manufactured by Daio Paper Corporation, product name: Ryuo Moisture-Resistant ST, air permeability: 146.2 sec / 100 mL)

[0070] (Experimental Example 1) [Preparation of electrolyte solution] An electrolyte solution (potassium hydroxide concentration: 17.6% by mass, sodium hydroxide concentration: 6.0% by mass) was prepared by adding potassium hydroxide (KOH) and sodium hydroxide (NaOH) as electrolytes to deionized water and mixing them.

[0071] [Fabrication of the positive electrode] A lattice made of foamed nickel with a porosity of 95% was prepared, and a positive electrode current collector was obtained by pressure molding the lattice. Next, predetermined amounts of cobalt-coated nickel hydroxide powder, metallic cobalt, cobalt hydroxide, yttrium oxide, CMC, PTFE, and deionized water were weighed and mixed, and the mixture was stirred to prepare a positive electrode material paste. At this time, the mass ratio of solids was adjusted to "nickel hydroxide:metallic cobalt:yttrium oxide:cobalt hydroxide:CMC:PTFE = 88:10.3:1:0.3:0.3:0.1". The moisture content of the positive electrode material paste was adjusted to 27.5% by mass based on the total mass of the positive electrode material paste. Next, the positive electrode material paste was applied to the positive electrode material support part of the positive electrode current collector and dried at 80°C for 30 minutes. After that, it was pressure molded using a roll press to obtain an unformed positive electrode having a positive electrode material layer.

[0072] [Fabrication of the negative electrode] A tin-plated steel plate perforated metal with a 60% porosity was prepared as the negative electrode current collector. Next, predetermined amounts of zinc oxide, metallic zinc, HEC, and deionized water were weighed and mixed, and the resulting mixture was stirred to prepare a negative electrode material paste. At this time, the mass ratio of solids was adjusted to "zinc oxide:metallic zinc:HEC = 85:11.5:3.5". AV-15F (product name) manufactured by Sumitomo Seika Co., Ltd. was used as the HEC. The moisture content of the negative electrode material paste was adjusted to 32.5% by mass based on the total mass of the negative electrode material paste. Next, the negative electrode material paste was applied onto the negative electrode current collector and dried at 80°C for 30 minutes. After that, it was pressure-molded using a roll press to obtain an unformed negative electrode having a negative electrode material (negative electrode material layer).

[0073] <Preparing the separator> For the separator, UP3355 (manufactured by Ube Industries, Ltd., trade name, air permeability: 638 sec / 100 mL) was used as the microporous membrane, and nonwoven fabric 1 was used as the nonwoven fabric. Before battery assembly, the microporous membrane was hydrophilized with the surfactant Triton-X100 (manufactured by Dow Chemical Co., Ltd.). The hydrophilization treatment was performed by immersing the microporous membrane in an aqueous solution containing 1% by mass of Triton-X100 for 24 hours, followed by drying at room temperature for 1 hour. The air permeability of the microporous membrane is shown as the value after the hydrophilization treatment. Furthermore, the microporous membrane was cut to a predetermined size, folded in half, and processed into a bag shape by heat welding the sides. One positive electrode (unformed positive electrode) and one negative electrode (unformed negative electrode) were placed inside the bag-shaped microporous membrane. The nonwoven fabric used was cut to a predetermined size.

[0074] <Manufacturing of nickel-zinc batteries> An electrode group (electrode plate group) was fabricated by laminating a positive electrode housed in a bag-shaped microporous membrane, a negative electrode housed in a bag-shaped microporous membrane, and a nonwoven fabric, and then connecting electrode plates of the same polarity with straps. The electrode group consisted of one positive electrode and two negative electrodes, with one nonwoven fabric placed between each electrode (between the microporous membrane on the positive electrode side and the microporous membrane on the negative electrode side). After placing this electrode group in a battery case, a lid was attached to the top surface of the battery case to obtain an unformed nickel-zinc battery. Next, the electrolyte was injected into the battery case of the unformed nickel-zinc battery and left for 24 hours. After that, charging was performed under conditions of 60mA for 15 hours to produce a nickel-zinc battery with a nominal capacity of 600mAh.

[0075] (Experimental Examples 2-5) In preparing the electrolyte, the electrolyte was prepared in the same manner as in Experimental Example 1, except that the type and amount of electrolyte used were changed so that the electrolyte composition (type and concentration of electrolyte) was as shown in Table 1. A nickel-zinc battery was then constructed in the same manner as in Experimental Example 1, except that the electrolyte obtained in this manner was used.

[0076] <Battery Performance Evaluation 1> The Coulomb efficiency and discharge performance of nickel-zinc batteries in Experimental Examples 1-5 were evaluated.

[0077] (Coulomb efficiency evaluation) A nickel-zinc battery with a state of charge (SOC) of 0% was charged at a constant voltage of 1.87V at 40°C for 24 hours, and the charge capacity (amount of electricity charged) was measured. Next, the nickel-zinc battery was discharged at a constant current of 120mA (0.2C) at 40°C to 1.1V, and the discharge capacity at 0.2C was measured. From the obtained charge and discharge capacities, the Coulomb efficiency (discharge capacity / charge capacity × 100) was calculated. A higher Coulomb efficiency indicates that side reactions were suppressed.

[0078] The aforementioned "C" represents the relative magnitude of the current when discharging the battery from a fully charged state to its rated capacity at a constant current. The aforementioned "C" means "discharge current value (A) / battery capacity (Ah)". For example, the current that can discharge the rated capacity in 1 hour is expressed as "1C", and the current that can discharge it in 2 hours is expressed as "0.5C".

[0079] (Discharge performance evaluation) Nickel-zinc batteries were charged at 25°C, 600mA (1C), and a constant voltage of 1.9V until the current decreased to 30mA (0.05C). Then, the batteries were discharged at constant currents of 30mA (0.05C) and 6000mA (10C) until the battery voltage reached 1.1V, and the discharge capacity was measured. The ratio of the discharge capacity at 10C to the discharge capacity at 0.05C (discharge capacity ratio (%)) was calculated. The results are shown in Table 1.

[0080] [Table 1]

[0081] (Experimental Example 6) An electrolyte solution (potassium hydroxide concentration: 30.0% by mass, lithium hydroxide concentration: 1.0% by mass) was prepared by adding potassium hydroxide (KOH) and lithium hydroxide (LiOH) as electrolytes to deionized water and mixing. A nickel-zinc battery was constructed in the same manner as in Experimental Example 1, except that the obtained electrolyte solution was used.

[0082] (Experimental Examples 7-11) A nickel-zinc battery was fabricated in the same manner as in Experimental Example 6, except that nonwoven fabrics 2-6 were used instead of nonwoven fabric 1.

[0083] <Battery Performance Evaluation 2> The cycle life and discharge performance of nickel-zinc batteries in Experimental Examples 6-11 were evaluated. The discharge performance was evaluated in the same manner as in Battery Performance Evaluation 1.

[0084] (Cycle life performance evaluation) A test was conducted in which nickel-zinc batteries were charged at 25°C, 600mA (1C), and a constant voltage of 1.9V until the current decreased to 30mA (0.05C), and then discharged at a constant current of 300mA (0.5C) until the battery voltage reached 1.1V. One cycle was defined as this process. The test was terminated when the discharge capacity fell below 50% of the discharge capacity of the first cycle, and the cycle life performance was evaluated based on the number of cycles performed until the end of the test. The number of cycles performed until the end of the test is shown in Table 2.

[0085] [Table 2]

Claims

1. a zinc battery electrolyte, which is an aqueous solution containing potassium hydroxide and lithium hydroxide; A plurality of separators having a total air permeability of 500 to 1400 sec / 100 mL; A zinc battery comprising a positive electrode and a negative electrode adjacent to each other with the plurality of separators interposed therebetween.

2. A zinc battery as described in claim 1, wherein the current collector in the positive electrode is made of foamed nickel.

3. The positive electrode material in the positive electrode contains a conductive agent, 3. The zinc battery of claim 1, wherein the conductive agent comprises a cobalt compound.

4. At least one of the plurality of separators is a hydrophilically treated microporous membrane, The zinc battery according to any one of claims 1 to 3, wherein the hydrophilically treated microporous membrane is in contact with the negative electrode.

5. The zinc battery according to any one of claims 1 to 4, wherein at least one of the plurality of separators has an air permeability of 0.1 to 150 sec / 100 mL.

6. The plurality of separators comprises three separators, The zinc battery according to claim 5, wherein the separator located on the positive electrode side and the separator located on the negative electrode side have an air permeability of 500 to 1000 sec / 100 mL.